Spontaneous alignment of crowded inferior incisives after the extractionof temporary canines - Orellana Manrique, Tomás Oriel (2008)
This investigation evaluated the behavior of permanent inferior incisives after the primary canine’s extractions. The study was carried out in the Pediatric Clinic of Dental Faculty of San Marcos University. The sample was conformed by 10 patients, male and female children, between 8 and 9 years of age, with good general health, having Class I malocclusion and severe crowding of the inferior incisives. It was taken Cephalometric and Panoramic radiographies, as well as models to make the orthodontic diagnoses and select the cases. To evaluate changes that took place in the area, models were prepared 3 months after extractions, having as a result: a complete correction of the inferior tooth crowding in 50% of the cases, a partial correction in 40% and any correction in 10%.